1988
DOI: 10.1128/jvi.62.4.1433-1436.1988
|View full text |Cite
|
Sign up to set email alerts
|

Processing protease and reverse transcriptase from human immunodeficiency virus type I polyprotein in Escherichia coli

Abstract: Expression of the human immunodeficiency virus type I pol open reading frame in Escherichia coli led to several protease-mediated processing steps of the pol precursor polyprotein. Accumulation of two polypeptides with molecular sizes of 64 and 52 kilodaltons, with which reverse transcriptase activity is associated, was observed. The protease moiety of the precursor polyprotein accumulated as a 10-kilodalton species as a result of two specific cleavages. Furthermore, a single-amino-acid substitution in the put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…For example, in the structures of RSV PR and the almost identical avian myeloblastosis associated virus (MAV) PR, there is a helical turn in this region that is not present in HIV-1 PR. Mous et al 35 reported that peptide antibodies were raised against the HIV-1 PR sequence in the range of residues 18-40. It may be suggested that such different surface structural features in different retroviral PRs can serve as an epitope for interactions with antibodies.…”
Section: Hydrophobic Interior Residuesmentioning
confidence: 99%
“…For example, in the structures of RSV PR and the almost identical avian myeloblastosis associated virus (MAV) PR, there is a helical turn in this region that is not present in HIV-1 PR. Mous et al 35 reported that peptide antibodies were raised against the HIV-1 PR sequence in the range of residues 18-40. It may be suggested that such different surface structural features in different retroviral PRs can serve as an epitope for interactions with antibodies.…”
Section: Hydrophobic Interior Residuesmentioning
confidence: 99%
“…2, 3b), although the conformation of this loop is predicted quite well. The modeling of this loop was aided by the good Table I1 and averaged for a) residues identical in RSV and HIV-1 PR sequences, b) functionally similar amino acid types (VIIIL; SIT; DINiEIQ occur), c) different types of amino acids, and d) residues forming the substrate binding site (8,9,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)76, 80-84, and 87). Then there is an analysis by type of amino acid segregated into e) polar sidechain in either RSV or HIV PR sequence, and f ) hydrophobic side chain in both RSV and HIV PR sequences.…”
Section: Comparison By Amino Acid Typementioning
confidence: 99%
“…In contrast with the NRTIs and NNRTIs, which were all discovered using cell-based assays, the PIs were rationally designed based on insight into the molecular mode of action of an aspartyl protease [57], and determination of their inhibitory potency in enzymatic assays. Recombinant DNA technology offered the best source to clone, express and purify the HIV protease [58,59], thus allowing the testing of potential inhibitors. Following the peptidomimetic lead, the hydroxyethylamine transition-state mimetic was clearly the best of those considered, leading first to the discovery of saquinavir [55] soon to be followed by indinavir, ritonavir and the other peptidomimetic HIV protease inhibitors [60][61][62][63].…”
Section: Protease Inhibitors (Pis)mentioning
confidence: 99%